Online teaching in an Indonesian higher education institution: Student’s perspective - Nova Lina Sari Habeahan; Seli Marlina Radja Leba; Wahyuniar Wahyuniar; Dina Br Tarigan; Sandra Ingried Asaloei; Basilius Redan Werang (International Journal of Evaluation and Research in Education (IJERE), 2022)
Online teaching has been pushed further as the best solution that addresses the challenges of colleges and universities closure during the COVID-19 pandemic. This study intended to disclose students’ perceptions of the online teaching. A quantitative survey approach was employed to collect data from a total of 175 students which were conveniently established from amongst students enrolled in academic year 2020/2021 at the Indonesian Language and Literature Education Department of Musamus University, Indonesia. Applying the SPSS software version 16 as the tool, obtained data were quantitatively analyzed using descriptive analysis of frequencies and percentages. The results showed the majority of respondent were disagreeing with the facts that they have an access to personal devices and that they can easily access to both internet and online classes. The majority of respondent were agreeing with the facts that teaching materials were well-planned and that various learning strategies were used to help students understand. The majority of respondent were agreeing with the facts that students were given opportunity to raise and answer the questions and that feedback given on students’ work are very helpful. Lecturers need to reach out and check students’ conditions before starting online teaching.